1994
DOI: 10.1677/joe.0.1430383
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of prolactin receptor mRNA expression in rat liver and kidney by testosterone and oestradiol

Abstract: Prolactin (PRL) exerts a wide variety of physiological effects on mammalian tissues through its receptor (PRL-R) on the target cells. PRL-R in rat tissue consists of two isoforms, the long and the short form, and the regulatory mechanisms of their mRNA expression in tissues are complex and diverse. The present study reports the differential regulation of PRL-R mRNA expression in rat liver and kidney by testosterone and oestradiol. Using Northern blot analysis, short form PRL-R mRNA was clearly detected in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…3B and C), at this stage PrlR expression is sex-independent in both hepatocytes and bile-duct epithelial cells. Further, in contrast to the sex differentiation of PrlR expression in hepatocytes (Sakaguchi et al 1994), in cholangiocytes the level of PrlR declines but remains sex-independent. Nevertheless, we have shown a low level of PrlR mRNA in cholangiocytes of mature male and female rats (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…3B and C), at this stage PrlR expression is sex-independent in both hepatocytes and bile-duct epithelial cells. Further, in contrast to the sex differentiation of PrlR expression in hepatocytes (Sakaguchi et al 1994), in cholangiocytes the level of PrlR declines but remains sex-independent. Nevertheless, we have shown a low level of PrlR mRNA in cholangiocytes of mature male and female rats (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Female and male sex hormones act on the alternative splicing of PrlR premRNA in rat hepatocytes in a unidirectional manner: they increase the preferential inclusion of the distal exon into mature mRNA (Table 3), although with different efficacies. The effect of oestrogens on alternative splicing resulting in preferential usage of the distal exon was demonstrated for growth hormone receptor pre-mRNA in mouse hepatocytes (Talamantes & Ortiz 2002) and for PrlR pre-mRNA in rat hepatocytes (Sakaguchi et al 1994). The level of long PrlR isoforms in normal cholangiocytes is almost equal to that found in hepatocytes of male and female rats (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It has also been shown that the expression levels of PRL-R mRNA in the different brain regions are regulated by oestrogen, which increases the utilization of E1 2 and E1 3 first exons (Pi et al 2003). In the liver, the expression of the PRL-R gene is known to be regulated by sex steroid hormones; up-regulation by oestrogen and down-regulation by testosterone (Jolicoeur et al 1989, Sakaguchi et al 1994. However, the molecular mechanisms of the effects of the sex steroid hormones on the expression of the PRL-R gene in the liver are not yet known.…”
Section: Introductionmentioning
confidence: 99%